Viscous fragmentation and topology-induced residual gas trapping during gas–water displacement in fracture networks - Kangsheng Xue; Hai Pu; Yanlong Chen; Ming Li; Yu Wu; Lulu Liu; Qingyu Yi; Zheng Ma (Advances in Water Resources, 2026)

Mechanisms of water-inrush mitigation under alternative grouting strategies during shaft sinking: Solidification-enabled stress–seepage–damage coupling - Wenxin Li; Dan Ma; Jiangyu Wu; Xuefeng Gao; Qiang Li; Changle Xu; Chuanjiu Zhang (Bulletin of Engineering Geology and the Environment, 2026)

A high-order bound-preserving finite difference multi-resolution WENO method for high-dimensional Richards equation - Xinyu Wu; Juan Cheng; Chi-Wang Shu (Advances in Water Resources, 2026)

Advancing citrus orchard soil health assessment through an environmental risk screening and multi-dimensional indicator integration framework - Zhenyu Wu; Jiayuan Wang; Yuzhi Zhou; Bao Cheng; Jie Zhang; Chang Chen; Marcelo J. Avena; Wenfeng Tan; Mingxia Wang (Applied Soil Ecology, 2026)

Intermittent oxygenation is essential for modulating nitrite ammonifiers in an agricultural upland soil to minimize nitrogen loss - Xiaogang Wu; Siyu Yu; Weikang Sui; Xinyu Zhang; Ji Li; Qiaoyu Wu; Xiaojun Zhang (Applied Soil Ecology, 2025)

The Role of Seaweed Cultivation in Integrated Multi‐Trophic Aquaculture ( IMTA ): The Current Status and Challenges - Yaojia Zhu; Nan Wang; Zhenyu Wu; Shuangshuang Chen; Ji Luo; George Christakos; Jiaping Wu (Reviews in Aquaculture, 2025)
Global mariculture production has witnessed sustained growth, yet intensive monoculture practices (primarily fish aquaculture) have generated increasingly severe environmental externalities, driving demand for sustainable solutions. Integrated Multi‐Trophic Aquaculture (IMTA), leveraging species synergy to recycle nutrients, emerges as a promising strategy. Seaweed plays a critical role as inorganic extractive species in IMTA. However, current large‐scale seaweed farming remains predominantly concentrated in Asia. Through literature review and synthesis, this paper mainly reveals the significance of seaweed in maintaining the ecological balance of the marine environment and improving co‐cultured species' production quality within IMTA. We also discuss the challenges faced by seaweed cultivation in IMTA, which include the following three parts: seaweed selection, IMTA setting and seaweed utilization, while highlighting emerging pressures from climate change. Analysis reveals greater controllability in land‐based IMTA systems versus open‐sea systems, where marine environmental complexity necessitates multidimensional considerations of seaweed species selection, cultivation area allocation, and temporal management. While envisioned as an eco‐economic “win‐win” solution, over‐optimistic projections of seaweed cultivation coupled with inadequate risk assessment may lead to short‐term successes followed by long‐term failures. For instance, although IMTA reduces environmental governance costs, hidden challenges—including seaweed's low market valuation, potential ecosystem perturbations, infrastructure requirements, and specialized labor demands—could paradoxically elevate systemic production costs. Future research requires dual assessment frameworks that concurrently evaluate ecological services and economic viability of seaweed cultivation in IMTA. More research and practical adjustments are needed to develop a long‐term, sustainable IMTA system.

A reinterpreted discrete fracture model for Darcy–Forchheimer flow in fractured porous media - Xinyu Wu; Hui Guo; Ziyao Xu; Yang Yang (Advances in Water Resources, 2023)